Etiology of Cyclocarya paliurus Anthracnose in Jiangsu Province, China - Zheng, Xiang-rong; Zhang, Mao-jiao; Shang, Xu-lan; Fang, Sheng-zuo; Chen, Feng-mao (Frontiers in Plant Science, 2021)
Cyclocarya paliurus is an extremely valuable and multifunctional tree species whose leaves have traditionally been used in used in medicine or as a medicinal tea in China. In recent years, anthracnose was has been frequently observed on young leaves of C. paliurusCy. paliurus in several nurseries located in Jiangsu Province, resulting in great yield and quality losses. To date, no information is available about the prevalence of C. paliurusCy. paliurus anthracnose in China. The main purpose of the present study was to characterize the etiology of C. paliurusCy. paliurus anthracnose. Phylogenetic analysis of the eightsix-loci concatenated dataset revealed that all 44 single-spore Colletotrichum isolates belonged to three species in the Colletotrichum gloeosporioides species complex, namely, C. aenigma, C. fructicola, and C. gloeosporioides sensu stricto. Phenotypic features, including the colony appearance and the morphology of conidia, appressoria and ascospores, were consistent with the phylogenetic grouping. Virulence tests validated that the three Colletotrichum species could cause typical symptoms of anthracnose on C. paliurusCy. paliurus leaves, similar to those observed in the field. The optimum mycelial growth temperature ranged from 25–30 °C for all representative isolates, while C. gloeosporioides s. s. isolates exhibited more greater tolerance to high temperature (40 °C). Fungicide sensitivity assays indicated that all three Colletotrichum species were sensitive to tetramycin, which may be a potential alternative for the management of C. paliurusCy. paliurus anthracnose. To our knowledge, this study provides the first report of C. aenigma, C. fructicola, and C. gloeosporioides s. s. causing C. paliurusCy. paliurus anthracnose in China as well as in the world.